FRECUENCIA DE LOS VIRUS PARA INFLUENZA-3, RESPIRATORIO SINCITIALY DIARREA VIRAL BOVINA EN UN REBAÑO MIXTO DE UNA COMUNIDAD CAMPESINA DE CUSCO - Cabello R., Karina (2012)
A serologic study was conducted to determine the prevalence of Parainfluenza-3 virus (PI3V), Syncytial Respiratoryvirus (RSV) and BovineViralDiarrhea virus (BVDV) in ruminants raised under harsh environmental conditions and poor management in the highlands ofCusco, Peru. Blood sampleswere collected in cattle (n = 66), alpaca (n = 21), and sheep (n = 152) for antibody detection against PI3V, RSV, and BVDV by serum neutralization test. The prevalence of PI3V, RSV, andBVDVwas 81.8, 87.8, and 90.9% in cattle, 50.0, 49.3, and 28.3% in sheep, and 23.8, 4.7, and 15.8% in alpaca respectively.The antibody titers ranged from2 to >256 and the highest titerswere found in bovine samples. The results indicate that these respiratoryviruses arewidely distributed in the animals of this rural community andmay play a key role in respiratory problems.